Characteristics and outcomes among pregnant women with end-stage renal disease on hemodialysis. (12th December 2022) - Lavie, Anat; Czuzoj-Shulman, Nicholas; Spence, Andrea R.; Abenhaim, Haim Arie
Abstract: Purpose: Pregnancy among women with end-stage renal disease (ESRD) has risen in frequency, which may be attributed to improvements in hemodialysis care. Our objective was to describe baseline characteristics and pregnancy outcomes among women with ESRD on hemodialysis. Methods: Using the United States' Healthcare Cost and Utilization Project-Nationwide Inpatient Sample, we created a cohort of women with ESRD on hemodialysis who gave birth between 2005 and 2015. We determined the proportion of adverse maternal and neonatal outcomes among this cohort. Then, we created a composite measure of vascular-mediated adverse pregnancy outcomes. Women who experienced at least one of either preeclampsia, intrauterine growth restriction, or intrauterine fetal death were categorized as having the composite measure. Then, multivariate regression models were used to estimate the associations between maternal baseline demographic and clinical characteristics and the composite measure. Results: Among 8, 765, 973 deliveries between 2005 and 2015, 307 were to women with ESRD on hemodialysis. Over the study period, the incidence of pregnancies to women with ESRD increased from 0.47 to 5.76/100, 000 births. An estimated 28% of pregnancies were complicated by preeclampsia, 8% by placental abruption, 58% delivered by cesarean, and in the postpartum, 28% required blood transfusions and 6% experienced sepsis. About 45% of babies were born preterm and 14% had IUGR. The composite measure of adverse events was not found to be associated with any baseline maternal characteristics. Conclusions: The frequency of pregnant women with ESRD on hemodialysis has risen, with adverse pregnancy complications for both mother and fetus. Transfer to high-risk centers is suggested for women with ESRD.